THE EFFECT OF TURNOVER ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Enggar Wulandari; Anggita Syahrani; Noverina Pretty Afrida; Laela Sa'bana Rani; Galuh Tri Pambekti (Universitas Wahid Hasyim, 2022)
This research aims to determine the effect of cash turnover, receivables, and supply on profitability in manufacturing companies. The independent variables used are Cash Turnover, Receivables Turnover, and Inventory Turnover. While the dependent variable used is Profitability. The population in this study is the financial statements of manufacturing companies totaling 120 companies over a period of six years listed on the Indonesia Stock Exchange (IDX) in 201 7-2020. Sampling is carried out by the proposive sampling method. The number of companies sampled in this study was 30 manufacturing companies. The analysis method of this study uses Linear Ordinary Least Square Regression (OLS) with a statistical analysis tool, namely the Eviews 8.0 program. The results of this study show that parally cash turnover has a significant effect on Return On Investment (ROI), receivables turnover has a significant effect on Return On Investment (ROI), and inventory turnover is not significant to Return On Investment (ROI). In terms of stimulant, the independent variables of cash turnover, receivables turnover, and inventory turnover together (simultaneously) significantly affect the Return On Investment (ROI) at α 1%.